INFLUENCE OF ETHAFOS ON ANIMAL ORGANISM - Dilbar Salimovna Vakhidova (European Science Publishing, 2024)
The use of insecticides against insects has two sides. On the one hand, it is possible to reduce the number of parasites, and on the other hand, insecticides can be excreted with milk, accumulate in internal organs and in blood. Therefore, our task was to study the effect of ethafos on the organism of animals after treatment of livestock premises with 0.3% aqueous suspension of ethafos and use of this preparation in the form of baits. It is noted that after wet treatment of the premises and body of animals there are insignificant changes in blood, as well as traces of drugs in muscles and liver.
Keywords: water emulsion, spraying of body and premises, insecticide baits, traces of drug, internal organs, hemocartin, hemoglobin, leukocytes, erythrocytes, aerosol treatment, zoophilic flies, experimental animals, control animals.